2010
DOI: 10.1029/2009jd013694
|View full text |Cite
|
Sign up to set email alerts
|

Solar dimming over the tropical urban region of Hyderabad, India: Effect of increased cloudiness and increased anthropogenic aerosols

Abstract: [1] The present work examines the multidecadal changes in the net downward shortwave radiation (NDSWR) over the urban region of Hyderabad, India, during the period . The trends in NDSWR and in cloud optical depth (COD) are analyzed over the region using the Modern Era Retrospective-Analysis for Research and Applications (MERRA 2D), which is a newly available data set. The NDSWR exhibits a significant reduction of ∼−20.25 W m −2 for the period 1993-2005; however, it declined at a slower rate (0.468 W m −2 ) dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 116 publications
(166 reference statements)
0
24
1
Order By: Relevance
“…The system employs an incremental analysis update (IAU) procedure (Bloom et al, 1996) to eliminate the shocks that are otherwise associated with the observations. Satisfactory agreement between MERRA products and observations from ground-based instruments or satellites has been observed over India (Badarinath et al, 2010;Gautam et al, 2011).…”
Section: Merra Re-analysismentioning
confidence: 89%
“…The system employs an incremental analysis update (IAU) procedure (Bloom et al, 1996) to eliminate the shocks that are otherwise associated with the observations. Satisfactory agreement between MERRA products and observations from ground-based instruments or satellites has been observed over India (Badarinath et al, 2010;Gautam et al, 2011).…”
Section: Merra Re-analysismentioning
confidence: 89%
“…Oguntunde et al [34] reported that Epan and solar radiation decreased significantly in all the months (p < 0.01) and the reduction ranged from 5.1% per decade in March to 9.3% per decade in August in Nigeria. Similarly Badarinath et al [35] found that the decline in solar radiation over Hyderabad in India was more intense during the period 1993-2005 compared to 1980s and attributed this to an increase in cloudiness mainly in monsoon. The Mann-Kendall test revealed increasing trend in monthly Epan except in March and June when Epan non-significantly decreased with year at Lome.…”
Section: Trends In Monthly Pan Evaporationmentioning
confidence: 99%
“…Such aerosols form thick layers of haze in winter, termed as Atmospheric Brown Clouds (ABC), which block the solar radiation reaching to the surface [101]. In [102], they have reported in their study over India that the AODs derived from TOMS data from 1979 to 2000 increased by ~11% per decade during the winter with large values over the IGB region, which consequently affect the surface reaching solar radiation, known as "solar dimming" [103][104][105]. The average solar dimming observed over India is about −0.86 W m −2 yr −1 , while during winter, pre-monsoon and monsoon seasons the same was observed to be about −0.94, −1.04 and −0.74 Wm −2 , respectively [104].…”
Section: Space-bornementioning
confidence: 99%